Embedded Platform for Generic High-order Sigma-delta Accelerometers Testing. (2016) - Brito, N.; Lima, V.; Alves, F.S.; Cabral, J.; Gaspar, J.; Monteiro, J.; Rocha, L.A.
Abstract: The transition from an open loop to a closed loop sensing approach in MEMS accelerometers is an important step towards improving the sensor noise performance, bandwidth and time responses[1] . However, this approach presents some computational challenges due to the fast nature of the mechanical part, and ultimately, the performance of the feedback circuit will establish the sensor performance limits that can be accomplished. This paper presents a processor-centric digital platform assisted by an FPGA for real-time control of MEMS accelerometers through a configurable multi-order ΣΔ modulation technology module. The system is designed to allow a high-level fine tune of the system control parameters, such as sensor offset, actuation voltage, sampling frequency, filters coefficients, ΣΔ order and coefficients as well as the output decimation ratio. The processor is used to control the hardware, perform time-critical synchronous operations and provide an external control port through a UART API protocol. The platform has been successfully tested in multiple ΣΔ configurations.